Validación de un protocolo fotográfico para la digitalización de muestras de herbario de especies tropicales - Valverde-Otárola, Juan Carlos; Quesada, Ruperto; Soto, Casia; Arias, Dagoberto (Revista Científica, 2020)
The study was validated of a photographic protocol for the digitalization of herbarium samples from digital colorimetry analysis. For which ten tree species were used in herbarium condition and belt types of shutter speed, objective aperture and ISO were evaluated in order to identify better fit and then identify the best photographic protocol from the variables L *, a *, b *, color differential (ΔE *) and chroma (ΔC *). The results showed that the shutter speeds of 1/3 ”, 1/5” and 1 ”showed ΔE * less than 5, considered as visible, the aperture of objective f / 5.6 and f / 7.1 showed ΔE * values ​​less than 5 , 5 being better adapted, while in ISO, values ​​100, 200 and 320 showed visible ΔE * values ​​and less than 5.3. As soon as the determination of the best protocol for the 10 species was CP1 with a speed of 1/3 ”, with an aperture of f / 5.5 and ISO 100 that presented an average ΔE * of 4.1 considered as visible and significantly lower than the rest of treatments that varied from 5.1 to 29.8, being changes from visible to total color and evidencing with color accumulations of 6 to 12 (ΔC *). Finally, IRF showed the users perceived that CP1 showed a better fit to the physical material (0.95) with respect to the other protocols (average 0.71).